Risk in Bond Investment and Risk Management Methods - Liu, Songmeiyi (Transactions on Economics, Business and Management Research, 2024)
Bonds play a pivotal role in the global financial markets, offering governments, corporations, and institutions a key funding source while providing investors with relatively stable income streams. However, bond investments are subject to several risks, including credit, interest rate, liquidity, and inflation. This research aims to explore the primary risks associated with investing in the bond market and present strategies to mitigate these risks. The paper highlights risk management methods such as diversification across different types of bonds, using credit default swaps, duration analysis to manage interest rate risk, and inflation-protected securities to combat inflation risk. By examining these techniques, this research provides a comprehensive guide for investors to minimise potential losses and optimise their bond portfolios. The findings contribute to the field by offering practical insights for investors, particularly those with lower risk tolerance, to make informed decisions that enhance risk-adjusted returns and ensure portfolio stability in uncertain market conditions.